Cardiac magnetic resonance parametric mapping can detect early cardiac involvement of patients with systemic sclerosis. (14th October 2021) - Purevsuren, M; Uehara, M; Ishizuka, M; Hara, T; Kakuda, N; Tsuji, T; Yamazaki, T; Hatano, M; Komuro, I
Abstract: Background: Systemic sclerosis (SSc) is divided into two subtypes, diffuse and limited cutaneous SSc (dcSSc and lcSSc). The dcSSc subtype has more severe internal organ fibrosis than lcSSc. It is unclear whether cardiovascular magnetic resonance (CMR) parametric mapping can detect early cardiac involvement in these two subtypes. Purpose: To detect cardiac involvement and evaluate differences between the two subtypes, we examined CMR parametric mapping. Methods: 57 consecutive SSc patients (27 dcSSc and 30 lcSSc) who visited our hospital from July 2018 to February 2021 and underwent CMR at 3.0T (Philips) were included. We analyzed myocardial damage using CMR parametric mapping and compared it with clinical data. Results: Mean disease durations of dcSSc and lcSSc were 4.0±6.5 years and 4.4±8.3 years, respectively. Although there were no significant differences in LVEF (56.8±8.8 vs 59.6±7.2), the left and right atrial volume index were significantly larger in dcSSc compared with lcSSc (all p<0.05). Focal fibrosis as evaluated by late gadolinium enhancement was found in 9 SSc patients (15.7%) and 4 patients had pulmonary hypertension. DcSSc patients had significantly higher mid-ventricular native T1 (1350.8±73.2 vs 1312.9±52.1, p=0.029) and postcontrast T1 values (640.4±59.4 vs 604.6±42.5, p=0.015) as compared to lcSSc, although there were no significant differences in ECV and T2 values. Native T1 values in mid-ventricular septum were positively correlated with E/e' ratio of echocardiography in overall SSc patients and dcSSc patients but not in lcSSc patients (r=0.320, p=0.021; r=0.505, p=0.010; r=0.195, p=0.329). Native T1 values in mid-ventricular septum were also positively correlated with plasma levels of brain natriuretic peptide (BNP) in overall SSc patients and dcSSc patients but not in lcSSc patients (r=0.353, p=0.008; r=0.484, p=0.011; r=0.113, p=0.559).The multiple regression analysis considering age and sex revealed that mid-ventricular septum native T1 was the independent predictor of E/e' in SSc patients (β=0.306, p=0.026), and dcSSc patients (β=0.553, p=0.007) but not in lcSSc patients (β=−0.282, p=0.105). The ROC curve for predicting E/e'≥14, cut-off value of native T1 in mid-ventricular septum was ≥1348.5msec (AUC 0.762; 95% CI 0.571–0.953; sensitivity 80.0%; specificity 68.1%). BNP was significantly higher in patients with native T1≥1348.5 msec compared with native T1<1348.5 (102.8±112.8 vs 45.7±55.7; p=0.014). The interobserver variability of CMR parametric mapping values was excellent in this study. Conclusion: DcSSc patients showed higher native T1 and larger left and right atrial volume index of CMR than lcSSc patients, suggesting that DcSSc patients had more severe myocardial involvement and left ventricular diastolic dysfunction than lcSSc patients. Early detection of the high native T1 may predict the occurrence of cardiovascular events in the future. Funding Acknowledgement: Type of funding sources: None.